Studies in systemic phonology - Tench, Paul (Bloomsbury Academic Collections. Linguistics. Open linguistics., 2015)
"This is the first collection of studies to apply the theory and techniques of Systemic Linguistics to the topics of phonology: descriptions of the pronunciation systems of languages - consonants, vowels, word accent, rhythm, intonation - and applications in speech synthesis, genre studies and broadcasting."--Bloomsbury Publishing